Dynamic characteristics of viscoelastic Mindlin plates with influence of temperature. (March 2020) - Litewka, Przemysław; Lewandowski, Roman
Highlights: The governing equations of the VE Mindlin plates in the Laplace domain are derived The simple procedure for dynamic characteristics of VE Mindlin plates is proposed. The simple method to include the temperature influence is included. Parametric studies of the dynamic characteristics are carried out. Abstract: This paper is devoted to geometrically linear free vibrations of viscoelastic (VE) Mindlin plates. The governing equations are derived in the Laplace domain. A simple way to take into account the influence of temperature on the damping properties is included using the frequency-temperature superposition principle. The novel approach to the solution of the non-linear problem of free vibrations of VE plates significantly simplifies the procedure reducing it to a linear eigen-value problem and a simple algebraic non-linear equation with one unknown. Several numerical examples involving varying physical parameters of the model are solved and the results are discussed.